Lost Books Reconstructing the Print World of Pre-Industrial Europe - Bruni, Flavia; Pettegree, Andrew (Library of the Written Word, 2016)
Questions of survival and loss bedevil the study of early printed books. Many early publications are not particularly rare, but many have disappeared altogether. Here leading specialists in the field explore different strategies for recovering this lost world of print. ; Readership: Scholars of early modern history, literature and religion, students of bibliography, book history. Advanced level undergraduates and postgraduate students with interest in these fields, members of the antiquarian book trade.